Reflect history changes of the famous historical building via AR technology - Beh, Jia Jing (2024)

(untitled)
The historical building is important treasure to our nation. The project address critical issues of historical building preservation in Malaysia. Understanding the reasons behind the current situation regarding historical buildings preservation become extremely important. According to the study, it shows most of the precious historical buildings in Malaysia is not getting adequate treatment which eventually leads to their demolition. To solve this problem, this project intent to reconstruct the demolished historical buildings using 3D model integrated with Augmented Reality (AR) while preserving the related information and store to provide an opportunity to the public in accessing and utilizing the knowledge. In order to develop a more integrated application, a review and analysis of past and existing applications is conducted, then based on the analysis of their weaknesses and strengths help us to strengthen our application. The development process is adopting the RAD methodology to enable a flexible development process. Additionally, the conduction of questionnaire also helps us to understand better the user requirements. The application is separate into different module to develop, which consists of AR Module, Building Module, Authentication Module, Map Integration Module, Bookmark Module, and Profile Module. Various software and technology are assisting the development of the application, such as the Visual Studio 2022, Blender, Unity, Vuforia SDK, Firebase and so on. The project visualizing the requirements in several stages, including user flow, storyboard, use case diagram, and so on. Finally, the application is being developed and evaluated on its effectiveness and functionality. The success of this project can bring a lot of benefits to the preservation of Malaysia’s historical treasures, allows it to pass generation by generation.